Analysis of High-Risk Factors Associated with the Progression of Subaneurysmal Aorta to Abdominal Aortic Aneurysm in Rural Area in China - Zhao W (Dove Medical Press, 2021)
Wenjun Zhao,1 Gang Wang,2 Ping Xu,3 Tingting Wu,3 Binjuan Chen,3 Haijun Ren,2 Xingjie Li1 1Department of Ultrasound, Imaging, Healthy Management Centre, The Second Hospital of Lanzhou University, Lanzhou City, 730000, Gansu Province, People’s Republic of China; 2Department of Neurosurgeon, Neurology, Neurologist, The Second Hospital of Lanzhou University, Lanzhou City, 730000, Gansu Province, People’s Republic of China; 3Department of Ultrasound, Imaging, Ultrasound Centre, The Second Hospital of Lanzhou University, Lanzhou City, 730000, Gansu Province, People’s Republic of ChinaCorrespondence: Xingjie LiDepartment of Ultrasound, Imaging, Healthy Management Centre, The Second Hospital of Lanzhou University, Landa 2 Yard, No. 82, Cuiying Gate, Chengguan District, Lanzhou City, 730000, Gansu Province, People’s Republic of ChinaTel +86-9318942555; +86-13609337887Email LiXingjie723723@163.comObjective: To determine the risk factors associated with the progress of subaneurysmal aorta (SAA) to abdominal aortic aneurysm (AAA) and provide a reference for the prevention of AAA in rural areas.Methods: A total of 747 SAA patients screened by the Health Management Center of the Second Hospital of Lanzhou University from January 2015 to January 2016 were recruited. The ratio of SAA progressing to AAA was observed through 5 years of follow-up. Logistic stepwise regression analysis was performed to analyze the high-risk factors. The relevant clinical prediction model score table (Nom) was made and the C-index and calibration chart were used to verify the prediction ability of the model.Results: Of the 747 patients diagnosed with SAA, 260 developed to AAA, with an incidence of 34.8%. Univariate analysis showed that age (62– 65 years old), abdominal aorta diameter greater than 2.7 cm, smoking after 30 years old, moderate to severe hypertension, and blood pressure variability were the important high-risk factors of SAA progressing to AAA. Logistic regression analysis showed that these factors were statistically significant. The nomogram of clinical prediction model score showed that when 50– 60% of SAA developed to AAA, the score was 189– 201 and the C-index was 0.883, verifying the moderate predictive ability of this model.Conclusion: Age, smoking habit, degree of hypertension, and control situation were high-risk factors associated with the progression of SAA to AAA. The control of the above high-risk factors was imperative for the prevention of AAA in rural areas without sufficient medical resources.Keywords: abdominal aortic aneurysm, high-risk factors, abdominal aorta dilation, rural areas